Effects of Selected Plants' Extracts on in vitro Growth of Rahtonia slanacearum (Smith), the Causal Agent of Bacterial Wilt of Irish Potatoes - Wagura, A. G.; Wangai, S. O.; Manguro L.; Gichimu, Bernard M. (Asian Network For Scientific Information, 2011)
The antibacterial effect of crude medicinal plant extracts of Ocimum gratissimum, Brassica oleracea var. botrytis and Ipomoea batatas on Rahtonia solanacearum (Smith) extracted from infected potato tubers was determined by in vitro study using ethyl acetate and methanol solvents. The extracts were used at concentrations of 0.4, 0.2, 0.1, 0.05 and 0.025 mg inL-1. It was found that all the plant extracts used at their different concentrations except methanol extracts oilpomea batatas at 0.025 mg mL_1 were effective to varying degrees in controlling the growth of bacterial colonies. The best results were observed with ethyl acetate extracts of Ipomoea batatas at concentration of 0.4 mg mL_1 giving mean inhibition zone of 4.2 mm followed by ethyl acetate extract of Brassica oleracea at concentration of 0.05 mg mL_1 that was 4.12 mm.
Keywords: Antibacterial effect, Rahtonia solanacearum, Brassica oleracea var. botrytis, Ipomoea batatas, Ocimum gratissimum